Prevalence and Molecular Characterization of Metallo β-Lactamase Producing Gram-Negative Pathogens Causing Eye Infections - Rameshkumar, Gunasekaran; Dhandapani, Ranjithkumar; Lalitha, Prajna; Rajapandian, Siva Ganesa Karthikeyan; Palanivel, Velmurugan; Thangavelu, Sathiamoorthi; Alyousef, Abdullah A.; Albalawi, Thamer; Alam, Pravej; Zubair, Mohammad; Saleh, Fayez M.; Alatawi, Fuad Abdullah; et al. (Frontiers in Public Health, 2022)
Purpose: Metallo β-lactamases (MβL) production is a worldwide problem, particularly in gram-negative bacteria. As scanty data are available on the prevalence of MBL, the present study is being undertaken to determine the prevalence, antibacterial sensitivity patterns and molecular characterization of MβL associated resistant genes in gram-negative bacteria isolated from ocular infections. Material and Methods: At a tertiary eye care centre in south India, 359 gram-negative pathogens, 200 isolates from eye infections, and 159 isolates from normal flora of the eye were studied. A gold standard microbiology method was used to identify the isolates. Antibiotic double disc synergy test and combination disc test were used to detect MβL production. Multiplex PCR was used to investigate the molecular characteristics of the MβL encoding genes blaVIM, blaIMP, and blaNDM. Results: Of the 359 gram-negative bacterial pathogens, Pseudomonas aeruginosa 108 (30.1%) and Enterobacter agglomerans 46 (12.8%) were commonly isolated. High prevalence of P. aeruginosa 81% (17 strains) was detected as an MβL producer and it shows 100% resistant to 2nd and 3rd generation cephalosporins and meropenem. Multiplex PCR detected only blaVIM gene in 56 (28%) from various eye infections and 27 (17%) from normal flora of the gram-negative bacteria (GNB). The blaVIM gene detected predominantly in 51.8% keratitis, and 21.4% postoperative endophthalmitis. High prevalence of gene was detected in P. aeruginosa 42.9% (24 of 56) and Alcaligens denitrificans 10.7% (6 of 56) from eye infections. Whereas in control group, P. aeruginosa and E. coli each 14.8% (4 of 27) were showed positive. Conclusion: The emerging MβLs mediated resistance among P. aeruginosa is a challenging task to ophthalmologists especially in patients with endophthalmitis and, bacterial keratitis. This local knowledge will aid in advising appropriate antibiotic use and avoiding unnecessary antibiotic prescriptions, which are highly warranted.